The evaluation of contemporary Azerbaijani poetry from the theme and problematic paradigm - Gulnara Javanshir Mammadzada (Research Retrieval and Academic Letters, 2024)
The unique development path of Azerbaijani poetry during the period of independence is determined, first of all, by the process of its formation in a new socio-political context. Poets and writers operating in a situation where socialist realism took a dominant position gained free and free creative opportunities during the period of independence and further developed the opportunities of integration with world poetry. Different creations of these literary forces, which are diverse in terms of generation, direction, style, trend, have not been so rich until now. The poetry of the independence period also attracts attention in terms of language, semantics and polysemy. The poetry of the period changed and updated not only in terms of subject matter and problematic, but also in terms of the mechanism of language processing, the formation of a new poetic language, stylistic shades, the breadth of the potential of expression, and the originality of the means of artistic representation. As new directions and currents appeared in poetry, its poetic structure and semantics also changed.